2002
DOI: 10.1159/000065590
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Resection- and Steroid-Associated Alterations in Gene Expression Were Not Accompanied by Changes in Lipid Uptake

Abstract: Background/Aims: Glucocorticosteroids alter the morphology and transport function of the intestine of adult rats. This study was undertaken to assess the possible effect on intestinal lipid uptake of the locally acting steroid budesonide, or the systemically active prednisone or dexamethasone. Methods: Sprague-Dawley rats underwent intestinal transection or 50% intestinal resection. Budesonide, prednisone, dexamethasone, or control vehicle was given for 2 weeks from the time of surgery. Uptake was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…55 56 However, this is not accompanied by the increased intestinal uptake of long chain fatty acids (LCFA). 57 Essential fatty acids may be required for optimal adaptation after resection. Rats fed fatty acid deficient diets had reduced mucosal hyperplasia compared with controls.…”
Section: Lipidsmentioning
confidence: 99%
“…55 56 However, this is not accompanied by the increased intestinal uptake of long chain fatty acids (LCFA). 57 Essential fatty acids may be required for optimal adaptation after resection. Rats fed fatty acid deficient diets had reduced mucosal hyperplasia compared with controls.…”
Section: Lipidsmentioning
confidence: 99%
“…Previous studies in adult rats also failed to show a correlation between changes in the intestinal lipid binding proteins and lipid uptake. 48 In addition, other workers have shown that a change in the abundance or a deficiency in I-FABP did not result in parallel alterations of intestinal lipid uptake. 49,50 Also, taking into account the complementary roles of L-FABP and ileal binding protein, it has been suggested that L-FABP is not necessary for lipid uptake into enterocytes.…”
Section: September-october 2004mentioning
confidence: 95%